Fetal echocardiographic markers to differentiate between a right and double aortic arch. (28th January 2022) - Van Poppel, Milou P. M.; Zidere, Vita; Simpson, John M.; Vigneswaran, Trisha V.
Abstract: Objectives: To describe the fetal echocardiographic features of a double aortic arch (DAA) and secondly, to assess the performance of these features to differentiate between a right aortic arch with left duct (RAA‐LD) in a blinded cohort of vascular rings. Methods: Review of records to identify surgically confirmed cases of DAA diagnosed prenatally from 2014 to 2018 (cohort‐A). Prenatal echocardiograms were reviewed and the segments of the aortic arches anterior and posterior to the trachea, aortic isthmuses and the presence/absence of the Z‐sign were described. The utility of these markers were assessed in a separate cohort (B) of fetuses with surgically confirmed cases of DAA or RAA‐LD. Results: Cohort‐A comprised 34 cases with DAA; there was a dominant RAA in 32/34 (94%) and balanced left aortic arch (LAA) and RAA in two cases. The proximal LAA was seen in 29/34 (85%), distal LAA in 15/34 (44%) and the LAA aortic isthmus in 4/34 (12%). The "Z" configuration was present in 29/34 (85%) cases. The most predictive marker for DAA in cohort‐B was the Z‐sign (sensitivity: 100%, specificity: 81%). Conclusion: The "Z" sign is a useful differentiator between RAA‐LD and DAA. The absence of visualization of the left aortic isthmus does not preclude the presence of a DAA. Key points: What's already known about this topic? Vascular rings are frequently identified on cardiac screening in the absence of major congenital heart disease Differentiation between double aortic arch (DAA) and right aortic arch (RAA) is important for postnatal management, but this is challenging with prenatal ultrasound due to the diminutive nature of the left arch of a DAA and difficult to achieve with postnatal imaging due to development of atresia of the distal left arch. This can lead to misreporting of associations and outcomes if the specific diagnosis is not made What does this study add? Accurate differentiation between RAA with left duct and DAA can be achieved with systematic ultrasound assessment In surgically confirmed vascular rings, the Z‐sign is a strong marker for a DAA even in those that develop atresia of the left arch The left aortic isthmus is rarely visualized in a DAA with fetal echocardiography and its absence should not preclude diagnosis of a DAA